JUSTIFICATION OF A RATIONAL METHOD AND EQUIPMENT FOR DRYING HIGH-MOISTURE SEEDS OF MELONS - TSURKAN, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The main reason holding back the wide distribution of pumpkin, like some other crops, is the lack of quality seeds. The receipt and storage of seed is largely dependent on the methods and means of drying. When choosing a technology and means for drying pumpkin seeds, one must take into account their adhesion properties, that is, the tendency to form conglomerates under certain conditions, sticking to working bodies, etc.Drying equipment should ensure uniform drying throughout the entire volume of products with different moisture content, as well as a change in the main process parameters - temperature and drying agent feed rate, which will allow the use of differential drying modes. But in drying installations used for grain processing, it is practically impossible to organize a high-quality process due to the impossibility of using differentiated modes of drying seeds, as well as increased cohesive-adhesive properties of the pumpkin seed layer. A much greater effect is achieved by devices with active hydrodynamic modes, in particular, in a fluidized bed with its modifications: an aerial boiling, vibroboiling and aerovibroboiling bed.In order to improve the flowability of a layer of materials prone to sticking, sticking, the formation of channels in the material layer, agglomeration, at the initial stage of drying, along with vibration and aeration mixing, it is advisable to use additional mechanical mixing devices.The article proposes a fundamentally new concept of energy-saving drying of high-moisture seed materials, in particular pumpkin seeds, the drying process of which through specific morphological, thermophysical, increased cohesive-adhesive properties, the presence of residues of the surface film and fruit in the seed layer is the most energy-intensive. At the first stage in the process of filtration drying, in which the heated drying agent under the influence of pressure drops moves through the cellular structure of the gas-permeable material, the drying of the material also occurs due to a change in the state of aggregation of the available, mainly surface, moisture. At the second stage, when the seeds acquire discrete properties, drying occurs in the aerovibroboiling layer due to the developed phase contact and an increase in the convective diffusion rate, which contributes to an increase in the drying rate in general and allows the process to be carried out at the maximum permissible values of seed heating.To carry out research to determine the rational technological parameters of the process, a structural and technological scheme of a vibration unit has been developed and a prototype has been created, which sequentially implements the filtration and convective stages of drying pumpkin seeds.
Keywords: melons; pumpkins; high-moisture seeds; vibrating dryers; filtration-convective drying; quality